ASSESSMENT OF THE PARTICIPATION OF MUSLIM WOMEN IN BUSINESS ACTIVITIES AND ITS IMPLICATION ON THEIR MATRIMONIAL OBLIGATIONS IN KADUNA STATE - Aliyu, Shafa'at Ahmad (Spektra: Jurnal Ilmu-ilmu Sosial, 2024)
This research was motivated by the proliferation of female Muslim in business activities in Kaduna State. Therefore, the research aimed at the involvement of Muslim women in business activities and its impact on their marital obligations among other objectives. In view of this, the study adopted a descriptive research design, and data were collected through a researcher-designed questionnaire for three categories of respondents: Muslim scholars, female Muslims, and husbands of Muslim women. A total of 400 respondents from four local government areas in Kaduna State participated in the study. The study revealed that the majority of scholars consider female participation in business activities permissible according to Shari’ah. This finding suggests that there is a consensus among scholars’ that Islamic law allows women to engage in business ventures. This recognition is important as it affirms the rights of women to actively participate in economic activities. The Qur'an does not explicitly prohibit women from engaging in business or attending to public functions but it emphasizes on keeping to moral values. While Islam encourages the establishment of strong family units and the fulfillment of marital responsibilities, it also recognizes the importance of individual aspirations and talents. Women's involvement in business activities is not inherently discouraged, but rather, it should be pursued with wisdom, balance, and adherence to Islamic principles.